Effect of Thermocycling on the Compressive Strength of Selected Luting Cements - Aws H., Al-Khadim; H., Abdullah; T., Al-Ani Sarah (IIUM Medical Journal Malaysia, 2018)
Introduction: The purpose of this in vitro study was to evaluate the effect of thermocycling on the compressive strength of selected luting cements. Material and methods: 5 types of luting cements were tested. A total of thirty cylindrical specimens measuring 6mm in height and 4mm in diameter were prepared for each type of cement which were then divided into two groups ie Group 1: Exposure, and Group 2: Control. Both groups were stored in distilled water at 37°C for 24 hours. Group 1 was subjected to 500 cycles in a thermocycling baths of 5ºC and 55ºC with 20 seconds in each bath. Group 2 was not exposed to thermocycling procedure. The compressive strength for each cement type was determined by using a universal testing machine. Results: Resin adhesive cement had the highest compressive strength; followed by conventional glass ionomer cement (GIC) whilst resin modified GIC was the least. Thermocycling had no significant effect on the compressive strength of RelyXTM ARC and Fuji I (p>0.05), but a significant effect on Fuji I CAPSULE, Fuji CEM, Fuji Plus CAPSLUE (p<0.05) was observed. Conclusion: The effect of thermocycling on the compressive strength of luting cements differed considerably with respect to their chemical compositions.